Conconavalin A-stimulated bovine T-cell supernatants inhibit growth of Cowdria ruminantium in bovine endothelial cells in vitro. - Mahan, S M (1994)
Conconavalin A-stimulated bovine T-cell supernatants inhibited the growth of Cowdria ruminantium in bovine endothelial cells in vitro but did not affect their entry. This finding represents one mechanism by which T cells may control C. ruminantium multiplication and hence affect the severity of disease.